PERSPEKTIF TRIANGLE FRAUD THEORY DALAM PENGADAAN BARANG/JASA DI PEMERINTAH PROVINSI NTB - Rinie Arifianti; Budi Santoso; Lilik Handajani (InFestasi, 2015)
This study examines the effect of ULP teamwork/ procurement officer characteristic, suitability compensation, and internal control system to government’s procurement fraud. The testing was held on 79 respondent who represent 32 percent population. Group respondent is ULP teamwork/ procurement officer at West Nusa Tenggara Provincial Government using the structural model analysis. The research findings showed that ULP teamwork/ procurement officer characteristic and internal control system had influence government’s procurement fraud, but is not affected by suitability compensation. ULP teamwork/ procurement officer characteristic and internal control system had negative influence to government’s procurement fraud. This means better ULP teamwork/ procurement officer quality and internal control system will reduce the occurrence of government’s procurement fraud. Research implication leads to improvement ULP teamwork/ procurement officer integrity and internal control system as a important part of preventing government’s procurement fraud.  The challenge of government’s procurement is the formulation policies that synergy with other regulation and improvement quantity and quality characteristics to improve performance government’s procurement.